소셜미디어를 활용한 기업 대상 연구 동향 분석 - 신유진(Yoojin Shin); 최보람(Boram Choi) (한국정보통신학회논문지, 2024)
This paper aims to analyze the trends of research conducted on companies using social media. Social media is one of the online platforms for sharing or exchanging individual thoughts, experiences, and opinions, and with the development of the IT environment, the use of social media has also grown rapidly. In recent years, research in the field of business administration or economics on the use of social media is also showing a significant increase. Contents posted on social media directly or indirectly affect corporate performance or corporate value. This study summarized the results of empirical research on this. This study proposes a technology-based convergence study on the economic effect of social media, and looks forward to expanding research in this field. KCI Citation Count: 0